The effect of multiplex-PCR-assessed major pathogens causing subclinical mastitis on somatic cell profiles - Goli, Mohammad; Ezzatpanah, Hamid; Ghavami, Mehrdad; Chamani, Mohammad; Aminafshar, Mehdi; Toghiani, Majid; Eghbalsaied, Shahin (Tropical animal health and production, 2012)
The major pathogens causing mastitis were evaluated by multiplex-polymerase chain reaction (M-PCR) with self-designed primers in four quarters of the first, third, and fifth parities in industrial, semi-industrial, and traditional dairy cattle farms in Iran. With the incidence of infection in the quarters by Staphylococcus aureus and Streptococcus agalactiae , the mean log somatic cell count (log SCC) increased from 5.06 to 5.77. The smallest changes occurred with Escherichia coli . Contagious pathogens, when compared with environmental pathogens, were more prevalent and common and created more profound quantitative and qualitative changes in SCC profiles. The second part of the study surveyed the diversity of contaminating pathogens and their effect on quantitative and qualitative profiles of somatic cells. M-PCR was used to determine the absence (M-PCR − ) and presence of one (M-PCR +1 ), two (M-PCR +2 ), and three (M-PCR +3 ) major pathogens in raw milk samples. Quarter log SCC increased from 5.06 (for M-PCR −1 ) to 5.5 (for M-PCR +1 ), 5.7 (for M-PCR +2 ), and 6 (for M-PCR +3 ). Percent changes in polymorphonuclears (PMNs) were not significant between different quarters and parities but were significant between different farms in terms of pathogen diversity ( P < 0.05). Therefore, by increasing the number of types of major pathogens involved in subclinical mastitis, SCC of udder quarters and the proportion of PMNs significantly increased, whereas the proportion of lymphocytes significantly decreased. This subject is very important in increasing the shelf life of dairy products, because PMNs are introduced to the enzymatic pools.